Optimization of M/M/2 Queueing Model with Working Vacations - Gupta, S.; Joshi, P. K.; Rajeshwari, K. N. (Journal of Scientific Research, 2023)
The paper deals with an M/M/2 Queueing Model with working vacations and reneging of customers due to impatience. The matrix geometric method is used to find the distribution of the number of customers in the system. A cost function is constructed to obtain the optimal value of the service rate to optimize (minimize) the cost function using the Quadratic Fit Search Method (QFSM). Further, the effects on the system's performance measures using numerical analysis and graphical representation are studied.